Autonomy and dignity of patients with dementia: Perceptions of multicultural caretakers. (February 2018) - Bentwich, Miriam Ethel; Dickman, Nomy; Oberman, Amitai
Background: A key message in the World Health Organization's report on dementia emphasizes the need to improve public and professional attitudes to dementia and its understanding, while acknowledging the fact that the workforce in dementia care is becoming increasingly diverse culturally. Objectives: To explore possible differences among formal caretakers from varied cultural background in their attitudes toward the autonomy and human dignity of patients with dementia. Research design: Semi-structured interviews and content analysis, utilizing two fictional vignettes for eliciting caretakers' attitudes toward dignity and autonomy of their patients. Participants and context: A total of 20 formal caretakers of patients with dementia from three different cultural groups in Israel ("Sabras, " "Arabs, " and "Russians"), working in nursing homes and a hospital. Ethical consideration: Approvals of relevant research ethics committees were obtained and followed. Findings: In comparison with the other groups, most Arab caretakers offer markedly richer perceptions of human dignity and autonomy. Their human dignity's conceptualization emphasizes "person-centered approach, " and their perception of patients' autonomy includes provision of explanations and preservation and encouragement of independence. Discussion: The differences found in the attitudes toward the meaning of autonomy and human dignity between the Arab caretakers and the other caretakers stand in contrast to previous studies regarding human dignity, emphasizing the common nature of these attitudes. Offering a linkage (theoretical and empirical) between the Arab perceptions of dignity and autonomy, the study strengthen and further the importance attributed in existing literature to person-centered care in enhancing the quality of care for patients with dementia. Conclusion: The conceptualization of human dignity may vary among different cultural groups. It may also influence the extent to which the caretaker holds a full-fledged perception of the patients' autonomy.